Evidences for a shift in barometric pressure, air temperature and rainfall patterns circa 1920, and its possible relation to solar activity - Sánchez Santillán, Norma; Esquivel Herrera, Alfonso; Sánchez-Trejo, Rubén (HIDROBIOLÓGICA, 2017)
A survey of 300 metereological stations worlwide located showed that nearly half of the stations presented a pattern change in the corelations between the sunspot number and barometric pressure, air temperature and precipitatio, around 1920. This change was mainly fom a negative correlation to a positive correlation. Furthermore, we also found strong correlations between sunspots and pressure and precipitation in both tropical and extratropical latitudes; for the temperature the strong correlations appear mainly in extratropical zones.